DO RADIOCARBON AGES OF PLANT WAX BIOMARKERS AGREE WITH 14C-TOC/OSL-BASED AGE MODELS IN AN ARID HIGH-ALTITUDE LAKE SYSTEM?. Issue 6 (23rd December 2021) - Aichner, Bernhard; Gierga, Merle; Stolz, Alexander; Mętrak, Monika; Wilk, Mateusz; Suska-Malawska, Małgorzata; Mischke, Steffen; Sachse, Dirk; Rajabov, Ilhomjon; Rajabov, Nasimjon; Rethemeyer, Janet
ABSTRACT: To elucidate the dynamics of terrestrial leaf waxes in a high-altitude lake system, we performed compound-specific radiocarbon analysis (CSRA) of long-chain n -alkanes in two sediment core sections from Lake Karakul (Pamirs, Tajikistan) and in surface soil samples from the catchment area. We aimed to answer the question whether the n -alkanes are delivered into the lake sediment with substantial delay due to storage in soils, which may cause a potential bias when used as paleoenvironmental proxies. In the surface soils, the CSRA results reveal an age range of n -alkanes from modern to 2278 ± 155 cal BP. In the two sediment core samples, three of the four n -alkane ages fell on the lower ends of the 1σ-uncertainty ranges of modeled ages of the sediments (based on AMS 14 C-TOC and OSL dating results). We conclude that sedimentary leaf waxes represent compounds with intermediate turnover time in soils, for example originating from alluvial plains close to the shores. Overall, the results provide evidence that sedimentary leaf wax compounds in this cold and arid setting are potentially older than the conventional age model indicates, but these findings need to be interpreted in context of the generally large uncertainty ranges of such age models.